The responsibility of the bank when refusing to meet the value of the check - CHEURFI, Khadidja (Journal of Human Sciences, 2020)
The bank is obliged to cash the check to the bearer once it is submitted to him. When the correct value of the check is refused and when the value of the correct check available on sufficient balance is refused, it will be held responsible to the collector, a contractual liability and to the bearer of the latter a tort liability, on this unjustified refusal. However, legal exceptions allow the bank to refuse this undertaking despite the fact that it has received a valid check, when it is unable to act in return for the execution of an opposition or seizure of the balance, its absence or insufficiency, and therefore the refusal of the bank to pay the check is legitimate.